Cytotoxicity of Gluconasturtiin and Its Derivative against MCF-7 and HepG2 - Konsue, Nattaya; Abdull Razis, Ahmad Faizal (KKU Science Journal, 2016)
The putative anticancer abilities of isothiocyanates, bioactive compounds in brassica vegetables, have been widely published. In the current study, gluconasturtiin, found naturally in watercress, and its derivative, phenethyl isothiocyanates (PEITC), toxicity against human breast cancer cells MCF-7 and hepatoma cell line HepG2 were determined employing MTT assay. A range of concentrations between 0-100 μM was used to study dose dependent cytotoxicity at 24, 48 and 72 hrs incubation periods. Paclitaxel at the same concentrations was served as a positive control. The results showed that in MCF-7 cell line, PEITC led to a time-dependent decrease in cancer cells viability with IC50 of 10.22, 3.61 and 2.68 μM at 24, 48 and 72 hrs, respectively, whereas those of HepG2 were 6.74, 4.22 and 4.19 μM. Moreover, gluconasturtiin had no effect on both cell lines at the concentration range studied. Apoptogenic effects of PEITC on MCF-7 were studied using fluorescence microscopy (AO/PI double staining). When cells were exposed to PEITC for 48 hrs at IC50 dose chromatin condensation and nuclear fragmentation were noticed. Moreover, apoptosis is one of chemopreventive mechanisms of PEITC which, however, toxicity on normal cells should be further investigated.